Identificação de genes associados com a eficiência na aquisição de fósforo em milho, com foco nos genes PSTOL1, STR1 e STR2 - Gabriel Corradi Azevedo (2015)
Low phosphorus (P) availability is a primary constraint for maize productivity, mainly in tropical soils. Considering the P fixation and low mobility in the soil, modifications on root morphology and association with arbuscular mycorrhizal fungi are important strategies adopted by plants to maximize soil exploitation under phosphorus starvation conditions. OsPSTOL1 was a gene associated to early root growth, P uptake and grain yield in rice. In order to identify putative homologs to OsPSTOL1 in maize, we combined comparative genomics and QTL mapping for root traits, seedling dry weight and P content in nutrient solution in a maize RIL population derived from the cross between two maize lines contrasting for P use efficiency, L3 and L22. Based on single and multi-trait models, 13 genomic regions were identified. Among the six predicted maize genes identified sharing more than 55% of amino acid sequence identity with OsPSTOL1, four genes were co-localized to QTLs on chromosomes 3, 4 and 8. These genes were more expressed in roots of the parental lines that contributed the alleles enhancing the respective phenotypes. Taken together, these results suggest that at least four of these candidates can be related to root morphology and P content in maize. Considering the mycorrhizal association, two half-size ABCG transporters, STR1 and STR2, were identified in rice and Medicago truncatula, as being indispensable to arbuscules development and, consequently, to mycorrhizal association success. Similar genes to STR1 and STR2 were identified in the maize genome, being co-localized to QTLs related to root morphology traits identified on chromosomes 10 and 3, respectively. The L3 and L22 lines showed a similar gene expression profile for both STR genes, as well high levels of root colonization and arbuscules well developed. The STR genes were expressed only in inoculated roots, following the same pattern as observed in rice. These results indicated a possible role of STR1 and STR2 to arbuscules development in maize and revealed that the difference in P use efficiency between L3 and L22 is not related to mycorrhizal association. However, additional studies are needed to validate these genes as functional homolog to OsPSTOL1, STR1 and STR2 in maize.